Exogenous application of stress-related signaling molecules affect growth and cannabinoid accumulation in medical cannabis (Cannabis sativa L.) - Garrido, José; Rico, Saleta; Corral, Carolina; Sánchez, Conchi; Vidal, Nieves; Martínez-Quesada, Juan José; Ferreiro-Vera, Carlos (Frontiers in Plant Science, 2022)
Medical cannabis (Cannabis sativa L.) is a source of bioactive phytochemicals with promising pharmacological and therapeutic applications. Enhancing the accumulation of valuable bioactive compounds is potentially a way of increasing the economic importance of this crop. Signaling molecules like salicylic acid (SA), jasmonic acid (JA), and γ-aminobutyric acid (GABA) are involved in the regulation of plant development and responses to biotic and abiotic stresses. Moreover, several phytohormones regulate plant trichome formation and elicit the synthesis of secondary metabolites in many plant species in both in vitro and in vivo systems. Therefore, exogenously delivered plant signaling molecules have the potential to modify the chemical profiles of medical cannabis. In this study, we found that the foliar application of SA, methyl jasmonate (MeJA), and GABA produces changes in the accumulation of the two major cannabinoids, cannabidiolic acid (CBDA) and Δ9- tetrahydrocannabinolic acid (THCA), in leaves and inflorescences of a medical cannabis variety. MeJA at 0.1 mM increased the CBDA content in inflorescences by 15.6%, while SA and MeJA at 0.1 mM increased CBDA and THCA accumulation in leaves by up to 57.3%. Treatments did not change the expression of genes participating in the final steps of the biosynthetic pathway of cannabinoids: olivetolic acid cyclase (CsOAC-1 and CsOAC-2), 2-acylphloroglucinol 4-prenyltransferase (CsPT4), cannabidiolic acid synthase (CsCBDAS), and tetrahydrocannabinolic acid synthase (CsTHCAS). Trichome density was not significantly different from the control plants in any treatment. Besides, we found strong correlations between several plant growth parameters and cannabinoid yields, showing a direct link between plant fitness and the production of cannabinoids.